2022
DOI: 10.1177/0272989x221096070
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Selecting “Time Zero” in External Control Arms with Multiple Potential Entry Points: A Simulation Study of 8 Approaches

Abstract: Background When including data from an external control arm to estimate comparative effectiveness, there is a methodological choice of when to set “time zero,” the point at which a patient would be eligible/enrolled in a contemporary study. Where patients receive multiple lines of eligible therapy and thus alternative points could be selected, this issue is complex. Methods A simulation study was conducted in which patients received multiple prior lines of therapy before entering either cohort. The results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In a comparative effectiveness study, multiple choices are available for when and how to set the time zero of follow-up [ 11 , 19 , 20 ], and the time-zero setting is particularly challenging in a study with a non-user comparator arm [ 12 ]. In this study, we implemented six methods to set time zero in a comparative RWD study with a non-user comparator and compared the effect estimates obtained from these settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparative effectiveness study, multiple choices are available for when and how to set the time zero of follow-up [ 11 , 19 , 20 ], and the time-zero setting is particularly challenging in a study with a non-user comparator arm [ 12 ]. In this study, we implemented six methods to set time zero in a comparative RWD study with a non-user comparator and compared the effect estimates obtained from these settings.…”
Section: Discussionmentioning
confidence: 99%
“…As such, various options are available for selecting time zero, but the proper selection is crucial to avoid time-related bias [ 11 , 12 ]. There are studies using simulated data [ 19 ] or RWD [ 20 ], which examined various approaches for selecting time zero, although they focused on time-zero setting of external control cohort with multiple line initiation as potential time zeros in oncology.…”
Section: Introductionmentioning
confidence: 99%
“…There are also cases where patients are eligible multiple times, for example, at the start date of the third and higher lines of treatment (Backenroth, 2021;Hatswell et al, 2022). In such cases, using all of the available data by allowing patients to enter the study at multiple timepoints (multiple baselines) may be an efficient solution, though more complex statistical methodology is needed to handle correlated data correctly.…”
Section: The Definition Of Baselinementioning
confidence: 99%
“…For an EC with an active comparator treatment, the assignment of time zero is generally straightforward: time zero begins at treatment initiation for all patients in the referent trial and the comparator arm. However, when patients in the comparator arm can meet eligibility criteria at multiple time points (e.g., because the comparator treatment strategy is 'no treatment' or is an active treatment that can be delivered in multiple treatment lines), there are a variety of approaches to defining time zero (Hernán and Robins, 2016;Kutcher et al, 2021;Hatswell et al, 2022). For specific situations, randomly assigning an eligible timepoint to patients in the EC arm, matching pre-treatment person-time between the EC and referent trial arms, and defining multiple time zeros across the study period by creating a series of nested trials have shown to be valid approaches to assigning index dates to patients in the EC arm.…”
Section: Time Zeromentioning
confidence: 99%
“…For specific situations, randomly assigning an eligible timepoint to patients in the EC arm, matching pre-treatment person-time between the EC and referent trial arms, and defining multiple time zeros across the study period by creating a series of nested trials have shown to be valid approaches to assigning index dates to patients in the EC arm. For a comprehensive evaluation of various approaches to selecting time zero in EC studies, refer to Hatswell et al (Hatswell et al, 2022).…”
Section: Time Zeromentioning
confidence: 99%